2011
DOI: 10.2320/matertrans.f-m2011817
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Foam Stabilization and Physical Properties of Particles on Aluminum Foam Production

Abstract: Experimental investigation of the foam stabilizing factors that influence aluminum foam fabrication is crucial to improve the foaming process. Solid particles contribute to an increase of the viscosity of the liquid phase and overall foam stability. Foam stability depends on the liquid type, wettability and the shape of solid particles. Even though a poor wettable particle contributes effectively to enhance liquid viscosity, the particle leads to the collapse of the foam cell due to the poor energy balance at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 20 publications
1
9
1
3
Order By: Relevance
“…If, however, the particle size of some of the component particles exceeds the inter-bubble lamellar thickness, and is not surface treated, whilst other particles can be housed within it, the large particle acts to distort the lamella, thus increasing the surface area contact between water and air, which then destroys the metastable equilibrium and the bubble will collapse. Our findings are in accordance with Kadoi and Nakae (2011) who demonstrated how the distribution and location of Al 2 O 3 and SiC particles depend on the energy balance at the solid-liquid interface and how the energy balance is influencing the formation of continuity between liquid and solid in foam systems [ 41 ]. It can be concluded that CNF acts as a structural skeleton in CNF-pigment foams due to gel formation and the intertwined gel-forming network.…”
Section: Resultssupporting
confidence: 92%
“…If, however, the particle size of some of the component particles exceeds the inter-bubble lamellar thickness, and is not surface treated, whilst other particles can be housed within it, the large particle acts to distort the lamella, thus increasing the surface area contact between water and air, which then destroys the metastable equilibrium and the bubble will collapse. Our findings are in accordance with Kadoi and Nakae (2011) who demonstrated how the distribution and location of Al 2 O 3 and SiC particles depend on the energy balance at the solid-liquid interface and how the energy balance is influencing the formation of continuity between liquid and solid in foam systems [ 41 ]. It can be concluded that CNF acts as a structural skeleton in CNF-pigment foams due to gel formation and the intertwined gel-forming network.…”
Section: Resultssupporting
confidence: 92%
“…It is considered that the hydrophobic particles can be attached on the liquid–gas interfaces and stabilize the foam bubbles in surfactant-free diluted suspensions 16 19 . Moreover, it is reported that the smaller particle leads to higher viscosity of the suspension under identical particle geometry and type 20 . Therefore, the high ICP concentration could be favor the foam stability because of modification of wettability of SiO 2 particles at the air–water interface and aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The easiness how the micro-sized particles react with the metal-matrix during melting and foaming to form intermetallic products that increase the viscosity of the melt is another drawback. Thickening and foam stabilization mechanisms can be assessed by quantifying the phases formed during the entire melt foaming process [ 51 , 52 , 53 ]. Phase analysis is also expected to shed light on foam fracture behavior [ 54 , 55 ].…”
Section: Composite Metal Foamsmentioning
confidence: 99%